Hypertension and Diagnosis of Parkinson’s Disease: A Meta-Analysis of Cohort Studies - Hou, Liyan; Li, Qiujuan; Jiang, Liping; Qiu, Hongyan; Geng, Chengyan; Hong, Jau-Shyong; Li, Huihua; Wang, Qingshan (Frontiers in Neurology, 2018)
Background: Hypertension has been associated with cognitive dysfunction in the general population and patients with Alzheimer’s disease (AD). However, there are contradictory data regarding the potential association between hypertension and diagnosis of Parkinson’s disease (PD), the second most common neurodegenerative disorder after AD. The purpose of this meta-analysis is to synthesize data from cohort studies to explore the potential association between pre-existing hypertension and subsequent PD diagnosis. Methods: The PubMed and Embase databases were searched to identify all relevant studies. Two independent investigators performed the data extraction. Eligible cohort studies providing risk and precision estimates related to hypertension and PD were selected. Pooled risk ratios (RRs) with 95% confidence interval (CI) were calculated by using a random-effects or a fixed-effects model. Sensitivity analyses after excluding one study at a time were performed to assess the stability of the results. Publication bias was assessed with Begg’s test and Egger’s test. Results: Seven cohort studies were identified, including 3170 persons who were confirmed to have developed PD and 339517 participants who did not have PD during follow-up. The onset of hypertension prior to PD diagnosis was significantly associated with an increased risk of motor stage PD (RR=1.799, 95% CI [1.066–3.037]). This relationship was further confirmed by secondary analyses based on estimates adjusted for potential vascular confounders (RR=1.319, 95% CI [1.073–1.622]). After excluding one study at a time, the sensitivity analyses still showed that hypertension history was significantly associated with an increased risk of motor stage PD (RR with 95% CI ranging from 1.11[1.075-1.35] to 1.42 [1.65-1.83]). No publication bias was observed in this meta-analysis. Conclusion: The findings of this meta-analysis suggest that hypertension may be a risk factor for motor stage PD, which may provide novel insights into the etiology and pathogenesis of this neurodegenerative disorder. However, large-scale well-designed studies that consider various confounders are still needed to further verify and clarify the association between hypertension and PD diagnosis.